Beginning JSF 2 APIs and JBoss Seam - Tong, Kent Ka Iok (Expert's voice in Java technology., 2009)
The Enterprise Java"!platform, Java EE 6, has gotten a facelift ... JavaServer"!Faces (JSF"! 2, is a big part of what's new in Java EE 6! JSF 2, a significant upgrade from JSF 1.2, includes Facelets and integration/use options with a variety of web frameworks, including the popular JBoss® Seam and even the Spring Framework. Beginning JSF"!2 APIs and JBoss® Seam gets you up to speed with the JSF 2.x API features and how they're implemented using the latest Seam web framework. This quick-start tutorial is the fastest way to get started on JSF 2, Facelets, and Seam, and with it you'll take the most useful features in the frameworks and apply them using best practices. You'll learn to create and enhance an eShop using practical methods, and can re-purpose the template for your own personal and professional projects